Implementation of Public Policies. Perspective of the Street Level Bureaucrats. A Re(view) - Rouquaud, Inés Mercedes; Rodríguez García, María Jesús; Herrera Gutiérrez, María Rosa (Revista del CLAD Reforma y Democracia, 2022)
The problems of public policy implementation, which arose in the North American school, have been and are a topic of concern for academics and scholars, giving rise to several approaches of analysis. The common denominator is the gap between policy objectives and their achievements. This gave rise to the so-called first-generation studies, which originate in the hierarchical or “top-down” view, based on the policy-administration dichotomy. The second generation of studies inverts the focus of the previous analysis and places it at the base of the organizational pyramid, giving rise to the “bottom-up” perspective. This is where the interest of this study is oriented, specifically from the proposal of Lipsky (1971 and 1980), who characterizes and defines public administration personnel at the base level as Street Level Bureaucrats (SLBs), defining the meeting space between bureaucrats and citizens (State and society), where public policies are considered to be executed. From there, multiple studies were generated, mainly in the United States and Northern Europe. However, in Latin America, empirical research on the subject is scarcer. The importance of the approach lies in the possibility of giving visibility to the problem of distribution of social services in a regional context with the need to overcome growing poverty and the problems of public management of most countries in low-income contexts. The paper proposes to review the Street Level Bureaucracy approach and of the most outstanding empirical works in relation to the implementation of social policies, both in the most widely applied countries such as the United States, the United Kingdom and Northern Europe, as well as in Latin American countries. The main interest is focused on the different institutional contexts of application of the theory and its divergences. The conclusions show the different trajectories, the evolution and expansion over time of the original version of the approach. Also, the need to expand research in Latin America, with adaptations to the context, without resigning institutional aspects.
Keywords: Public Policy; Policies Implementation; Bureaucracy; State-Society Relationship; United States; United Kingdom; Europe; Latin America